Building Nationalities within Christians Virtues - Julinda Asap Suluh; Lukas Lukas; Yesyurun Munthe; Yulista Yulista (Yayasan Adra Karima Hubbi, 2024)
Background. Reflecting Pancasila in research world not necessarily discussing Indonesian citizenship as a civil society, these discourses widened to theological settings, particularly scriptural texts that are often used as sermons in pulpits. Indonesian ideological issues encountering Christianity have flowed and led to the entanglement of structural issues. Purpose. The aim of research was to explore the threads of nationalism in Pancasila, specifically crossing over with Christian values. Method. Based on qualitative research, researchers searched data through previous writings relevant to Pancasila, education, scriptural texts and their history. Results. Results showed that Christianity has brought goodness news not just limited to Christians, but also brought light for the world as reflections of socialist human beings. It must be understood that Indonesian nationalism is nationalism that rejects all forms of discrimination, oppression, injustice, and denial of divine values, as contained in Pancasila. Conclusion. Citizens have four main roles in the nation and state, namely as iron stock, social by control, agent of change, and also moral force. Those four main roles in running the life of the state are certainly not at all contradictory to Christianity. By performing these four roles, Christians show the quality of their Christian faith by becoming good citizens.